2015
DOI: 10.3354/dao02907
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus-like respiratory infection in African penguins Spheniscus demersus admitted to a rehabilitation centre

Abstract: Rehabilitation is an important strategy for the conservation of the Endangered African penguin Spheniscus demersus, and disease has been raised as a concern in the management of the species, both in the wild and in rehabilitation centres. We report 8 cases of herpesvirus-like respiratory infection in African penguin chicks undergoing rehabilitation between 2010 and 2013 at a facility in Cape Town, South Africa. Infection was confirmed through the identification of viral inclusions in the tracheal epithelium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The lack of detection of antibodies against Gallid alphaherpesvirus 1 and Gallid alphaherpesvirus 2 was not unexpected, considering that Galliformes and Anseriformes are the only known hosts to these viruses (García et al 2013;Schat and Nair 2013), and that previous serological and PCR surveys in penguins also failed to detect their circulation (Miller et al 2001;Travis et al 2006;Smith et al 2008). Previous studies show that some respiratory herpesviruses infecting penguins may elude detection by serological and molecular tests targeting gallid alphaherpesviruses (Parsons et al 2015). Therefore, the negative results in this study should not be interpreted as an absence of exposure to other putative herpesvirus species such as Magellanic penguin herpesvirus 1 and Magellanic penguin herpesvirus 2, the latter recently reported in several colonies included in this study (Niemeyer et al 2017).…”
Section: Herpesviridaementioning
confidence: 96%
“…The lack of detection of antibodies against Gallid alphaherpesvirus 1 and Gallid alphaherpesvirus 2 was not unexpected, considering that Galliformes and Anseriformes are the only known hosts to these viruses (García et al 2013;Schat and Nair 2013), and that previous serological and PCR surveys in penguins also failed to detect their circulation (Miller et al 2001;Travis et al 2006;Smith et al 2008). Previous studies show that some respiratory herpesviruses infecting penguins may elude detection by serological and molecular tests targeting gallid alphaherpesviruses (Parsons et al 2015). Therefore, the negative results in this study should not be interpreted as an absence of exposure to other putative herpesvirus species such as Magellanic penguin herpesvirus 1 and Magellanic penguin herpesvirus 2, the latter recently reported in several colonies included in this study (Niemeyer et al 2017).…”
Section: Herpesviridaementioning
confidence: 96%
“…The pattern of lesions found in penguins, including the presence of intranuclear inclusion corpuscles and clusters of syncytial cells with amphophilic core, is consistent with the pattern of disease described for the Iltovirus genus, such as Gallid herpesvirus 1 (GaHV -1) or laryngotracheitis virus of chickens, and Passerid herpesvirus 1 (PaHV-1) or tracheitis-causing virus in Gouldian Finch ( Erythrura gouldiae ), which was also considered in the phylogenetic analysis (Fig 4) [2, 14]. Although a herpesvirus-like infection had been described in captive African penguins in the Baltimore Zoo, United States [6], and in South Africa [7], the occurrence of herpesvirus infection in penguin species is likely uncommon. The CRAM rehabilitation centre in Brazil has operated for the past 30 years without any similar mortality outbreak as the one reported here.…”
Section: Discussionmentioning
confidence: 99%
“…A herpesvirus-like infection affecting African penguins was first described at two sites, the Baltimore Zoo [6] and at a rehabilitation facility in South-Africa [7]. In both cases the authors suggested a herpesvirus infection due to clinical and histopathological alterations, but virus isolation and DNA sequencing was not achieved.…”
Section: Introductionmentioning
confidence: 99%
“…There were no positive samples in serology testing for ILTV (also known as gallid herpesvirus 1) despite previous evidence that African penguins are susceptible to herpesvirus-like infections (Kincaid, Bunton & Cranfield 1988 ; Parsons et al . 2015a ). Previous studies on other penguin species have also failed to identify antibodies against this virus (Karesh et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the occurrence of herpesvirus respiratory infections at the same facility (Parsons et al . 2015a ), a limited number of samples were submitted to Agrilabs (Pioneerfoods [Pty] Ltd, Malmesbury, South Africa) to be tested for infectious laryngotracheitis virus (ILTV, also referred to as gallid herpesvirus 1) through indirect ELISA.…”
Section: Methodsmentioning
confidence: 99%